Analisis Tingkat Kerusakan Hutan Mangrove Berdasarkan NDVI dan Kriteria Baku di Kawasan Hutan Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Yohanes Risky Shellen Ginting; Anita Zaitunah; Budi Utomo (Peronema Forestry Science Journal, 2015)
The activities of people caused the high rate of mangrove degradation in Percut Sei Tuan District Deli Serdang Regency. The activities were found such as marine aquaculture in ponds, new settlements, or the oil palm plantations. It will disturb the mangrove ecosystems and coastal ecosystems that are essential for the existence of migratory birds as well as wildlife habitat in water as spawning ground, nursery ground, and feeding ground areas. It also functions as a barrier for abrasion and seawater intrusion. This study seeked to analyze the extent of degradation in mangrove forests in Percut Sei Tuan District. There were two methods as well as direct and indirect. Direct analysis was intended to see degradation level of mangrove forest based on analysis in the field and then analyzed again the degradation rate, which refered to the Decree of the Minister of Environment of Indonesia, Number 201/2004 on the Criteria and Guidelines for Determining Damage of Mangrove Forests. The indirect method was to perform the analysis of degradation level of mangrove forests based on NDVI (Normalized Difference Vegetation Index) using Landsat 8 satellite image. This research was expected to give figures of the current mangrove forest in Percut Sei Tuan District and the degradation level. The results showed that mangrove forest in Percut Sei Tuan District in damage category with 4.161% of crown closure and there was 168.7 ha in damage category based on NDVI value.Keywords : mangrove degradation level, NDVI, standard criteria, Percut Sei Tuan